A Study of Cooperative Learning and Independence: Impact on Children's Prosocial Behavior - Yulianto, Dema; Yufiarti, Yufiarti; Akbar, Ma'ruf (International Journal of Education, 2019)
The purpose of the study was to analyze the impact of cooperative learning with the PAP and STAD methods and independence on young children's prosocial behavior. The research used an experimental method. The sample consisted of 48 children. Data were analyzed with the 2-factor ANOVA variants, followed by an interaction test between variables using the Tuckey test. The results show that there were differences in the prosocial behaviors between the group of children with high and low independence. Different method of cooperative learning used influenced young children’s prosocial behavior diffierently. There was also an interaction between cooperative learning and independence towards young children’s prosocial behavior. The implication of this research is that teachers as educators and counselors are required to carry out systematic and ongoing prosocial education as a form of example for children. Teachers wishing to teach with cooperative learning should choose a method appropriate to children’s characteristics. In addition, it is important to increase teachers’ motivation in teaching.